2020
DOI: 10.1088/1402-4896/ab4335
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional finite-element simulations of the diffusion and trapping of hydrogen in plasma-facing components including thermal expansion

Abstract: This study is focused on tritium retention and permeation through a 316L stainless steel diagnostic first wall during plasma operations in ITER. A set of data for migration properties are proposed by adjusting these values to fit a simulation with experimental results. A reactive-diffusion model coupled with mechanical field, solved on 3DS Abaqus finite element software, is applied to estimate tritium migration. The interest of 2D simulations compared to 1D simulations are shown and the role of thermal expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…As described in previous studies 5 , 7 9 , the macroscopic rate equations model used in this work splits hydrogen isotopes into two populations: the mobile particles and the trapped ones. The temporal evolution of mobile particles and trapped particles in the i-th trap are described in Eqs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in previous studies 5 , 7 9 , the macroscopic rate equations model used in this work splits hydrogen isotopes into two populations: the mobile particles and the trapped ones. The temporal evolution of mobile particles and trapped particles in the i-th trap are described in Eqs.…”
Section: Methodsmentioning
confidence: 99%
“…The trap parameters are described in Table 2 . Influence of mechanical fields such as thermal expansion on trap creation 7 was not taken into account in this work. Hodille et al described an extrinsic trap in tungsten created by ion implantation 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Kanayama et al showed that this formulation produces drastically different hydrogen distribution when compared to the use of Oriani's equilibrium theory, particularly when the loading time is significantly small (or the strain rate is high). Their approach has been used in several recent works [16,[24][25][26][27][28]. However, the assumption of a constant trap density in equation ( 6) appears to be problematic considering the evolution of trap density with plastic strain used in equation ( 8).…”
Section: Expressions Of the Trapped Hydrogen Concentration Ratementioning
confidence: 99%
“…These partial derivatives have been evaluated by Benannoune et al [24] using an approximation of the solution of the McNabb and Foster differential equation (see below equation ( 3)). This approach was used to solve initial boundary values problems involving transient hydrogen trapping processes, either without trap creation (e.g., on Thermal Desorption Spectroscopy spectrums), or for more complex problems, in which hydrogen diffusion, and transient trapping have been coupled with evolving (thermo)mechanical fields [25][26][27][28]. The present study aims at extending the work of Krom et al [2] to transient trapping by improving the formulation proposed by Kanayama et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen transport and trapping is classically described by the diffusion formulation proposed by (Sofronis and McMeeking, 1989) and later improved by (Krom et al, 1999;Sofronis and McMeeking, 1989) (see below section 4.2.2), applied on a Small Scale Yielding configurations. This approach has been implemented in commercial or home-made finite element software, coupled (or not) with mechanical fields, and used in numerous studies to investigate specific features of hydrogen-material interactions in homogeneous structures, including embrittlement or interactions with thermal fields (not being exhaustive, e.g., to study the plastic strain localization during a tensile test on steel (Miresmaeili et al, 2010), to analyze the permeation test on steel samples (Legrand et al, 2012), to model or analyze crack propagation (Takayama et al, 2011) or hydrogen repartition after welding in steel pipes (Yan et al, 2014), after welding in steel pipes, or to analyze the effect of a thermomechanical field in a tungsten plasma-facing component (Benannoune et al, 2019a)).…”
Section: Introductionmentioning
confidence: 99%